2007
DOI: 10.1161/circulationaha.107.706770
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Untwisting Rate by Speckle Tracking Echocardiography

Abstract: Background-Recent studies validated the measurement of left ventricular (LV) untwisting rate (UR) by speckle tracking echocardiography. A few reports suggest that it may provide additional noninvasive insight into LV diastolic function. Methods and Results-Simultaneous echocardiographic imaging and LV pressure measurements (7F Millar catheters)were performed in 8 adult dogs. Loading conditions were altered by caval occlusion, whereas lusitropic state was changed by dobutamine and esmolol infusion. Inferior ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
132
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 28 publications
17
132
2
7
Order By: Relevance
“…Speckle tracking is the preferred technique given its angle independence and higher reproducibility; however, studies utilising this modality have demonstrated incongruent results. Wang, et al 157 demonstrated that in HF patients, LV twisting and untwisting rates were reduced in patients with reduced LVEF but not in those with HFNEF. The onset of untwisting was significantly delayed in both systolic and diastolic HF.…”
Section: Torsion/twist Mechanicsmentioning
confidence: 99%
“…Speckle tracking is the preferred technique given its angle independence and higher reproducibility; however, studies utilising this modality have demonstrated incongruent results. Wang, et al 157 demonstrated that in HF patients, LV twisting and untwisting rates were reduced in patients with reduced LVEF but not in those with HFNEF. The onset of untwisting was significantly delayed in both systolic and diastolic HF.…”
Section: Torsion/twist Mechanicsmentioning
confidence: 99%
“…61,62 This may be related to an increased interstitial collagen with lack of change in the MMP-1/TIMP-1 ratio and a higher ratio of shorter (stiffer) N2B isoform to longer (more compliant) N2BA titin isoform, a giant sarcomeric cytoskeletal protein that extends from the Z-lines to the centre of the thick filament and functions as a molecular spring, contributing to the high resting passive stiffness of the myocardium 63,64 and perhaps to the higher restoring forces and preservation of untwisting of the LV (see below). 65 Does HHD evolve as concentric LVH with HFNEF and transition to SHF with LV dilation and reduced EF?…”
Section: Patterns Of Hypertrophic Remodellingmentioning
confidence: 99%
“…Potential energy stored by LV twist during the systolic phase is rapidly released during LV untwisting and constitutes an important determinant of diastolic suction and function [5]. Two-dimensional speckle tracking imaging (2D--STI) is a novel ultrasound technique for quantification of LV regional deformation, myocardial rotation, torsion, twist and untwisting [6,7]. This technique has been validated by tagged magnetic resonance imaging, which is currently considered gold standard for the assessment of myocardial rotational parameters [8,9].…”
Section: Introductionmentioning
confidence: 99%